Methodological aspects of research on tourist activity – new concepts - Różycki, Paweł (Geotourism/Geoturystyka, 2025)
Research on tourist activity is considered to be particularly troublesome. Due to the lack of one, coherent definition of tourism there occur considerable problems the results of studies carried out in various research centres are compared. Theintensity of the problem increases in the case of the research on tourist activity in physical culture, sociology and psychology. In this study a new, so far not applied, definition of tourist activity is presented. It could be helpful in research on tourism, based on criteria of distinguishing between tourists. A subjective criterion allows us to distinguish between people who feel they are tourists, and who subjectively feel that what they do can be regarded as the phenomenon of tourism.